Design, synthesis and evaluation of MCH receptor 1 antagonists—Part I: Optimization of HTS hits towards an in vivo efficacious tool compound BI 414. Issue 16 (15th August 2015) - Müller, Stephan G.; Heckel, Armin; Kley, Jörg T.; Lehmann, Thorsten; Lustenberger, Philipp; Oost, Thorsten; Roth, Gerald J.; Rudolf, Klaus; Arndt, Kirsten; Lenter, Martin; Lotz, Ralf R.H.; Maier, Gerd-Michael; et al.
Graphical abstract